Leak Monitoring Prototype and Gas Availability in CO2 Type APAR (Light Fire Extinguisher) - Huda, Samsul; Ilmi , Muh. Bahrul (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
Fire  safety  is  an  important  aspect  that  must  be  considered  when  in  a  building.  A lightweight  fire  extinguisher (APAR)  is  a  piece  of  mandatory  standard  equipment  for  building  safety.  Therefore,  it  requires  maintenance operations  to  ensure  the  fire  extinguisher  is  functioning  properly  whenever  needed.  This  monitoring  activity  is still done manually with human power. Moreover, these standard controls and checks are often neglected. In this study,  we  propose  a  prototype  of  the  gas  availability  monitoring  system  for  CO2-type  fire  extinguishers.  We adopt  NodeMCU  esp8266  as  processor,  gas  sensor  as  CO2  reader  and  buzzer  as  output.  This  design  serves  to detect  the  level  of  CO2  concentration  around  the  location  of  the  extinguisher  tube  placement.  The  system  will also sound a buzzer and send a notification via telegram when the CO2 concentration reading is not within the normal range, which means a gas leak has occurred. Features and services have been validated through two test scenarios